Functional outcomes of tibiotalocalcaneal arthrodesis using a hindfoot arthrodesis nail in treating Charcot's arthropathy deformity - Bajuri, Mohd Yazid; Manas, Ammar Muizuddin; Zamri, Kamarul Syarazi (Frontiers in Surgery, 2023)
Background Tibiotalocalcaneal arthrodesis or hindfoot fusion is a salvage surgical option used to treat symptomatic or severe deformity as a result of Charcot’s arthropathy. It is an internal fixation that utilizes nails to stabilize the hindfoot after surgical correction of the deformity. This study intends to measure the change in functional outcomes of patients with Charcot's arthropathy using this technique and the time taken to achieve fusion. Method This study presents a series of 40 cases of Charcot's arthropathy where hindfoot fusion was done using a hindfoot arthrodesis nail. A retrospective analysis was done where these patients’ functional scores had been evaluated preoperatively and postoperatively (serially) with the Short-Form Health Survey 36 (SF-36), American Orthopedic Foot and Ankle Society (AOFAS), Foot and Ankle Outcome Score (FAOS), and Foot Function Index (FFI). Along with its complication, the length of time required for the fusion is also reported. Results This study consists of 40 patients (13 men, 27 women; mean age 60.5 years; age range 52–68 years) with a mean follow-up of 64 months (range 24–108 months). The mean time taken for fusion was 5.1 months. All patients showed improvement in functional scoring (SF-36, AOFAS, FFI, and FAOS) postoperatively. We establish that the improvements were gradual over 2 years. Approximately 37.5% of patients had a minor complication and 2.5% had a major complication. Conclusion Hindfoot fusion using a hindfoot arthrodesis nail results in improved functional outcome with an acceptable fusion time and acceptable complication rate. Level of evidence Level III.